Treatment with enhanced external counterpulsation improves cognitive functions in chronic heart failure patients - Güliz Kozdağ; Pervin İşeri; Gökçen Gökçe; Gökhan Ertaş; Fatih Aygün; Ayşe Kutlu; Kathy Hebert; Dilek Ural (KARE Publishing, 2013)
Objectives: Chronic heart failure (CHF) has been associated with an increased risk of poorer cognitive performance in older adults. Reversibility of cognitive impairment after medical treatment has been reported, although the restorative effects of enhanced external counterpulsation (EECP) on cognitive performance have not been studied. We investigated the effect of EECP on cognitive functions in CHF patients. Study design: Thirty-six individuals (mean age: 66+-8 years) who were diagnosed with CHF and were New York Heart Association (NYHA) Class II-III and Canadian Cardiovascular Society (CCS) Class II-III participated in this study. Neuropsychological assessment was performed in these patients. Results: Patients in the EECP treatment group showed a statistically significant improvement in spontaneous naming (p=0.011) and forward row score of the attention subset among domains of cognition (p=0.020) and interference time of executive function (p=0.012). Conclusion: Enhanced external counter pulsation resulted in improvement in all domains of cognitive functions except verbal and visual memory tests.